مساهمة الدكتور محمد رمضان عبد الله (رحمه الله) في تجديد علم الكلام من خلال كتابه الباقلاني وآراءه الكلامية - جدوع احمد الجبوري عوض; عبود علوان أحمد (Journal of College of Education, 2020)
The Iraqi speech school is considered prominent & contemporary in Arabic & Islamic verbal thought . This school gave much about the Islamic verbal heritage, through achieving & publishing. For the privacy of the school much was given about the verbal Science & establishing independent projects. The context reveals the study about Dr. Muhammad, by describing an attempt to show the new aspects in verbal Science. The study was divided in two topics: The first one :(is from the old science of speech to the new one ),through Dr. Muhammad a concept of the new speech science is explored by comparing his views & references. The second one : is about renewal his topic by studying the book aspects through the following: Introducing his book . The methodology of the book writing. His traditional criticism. His method in presenting the issues. It’s about the style. The conclusion includes important results & recommendations .(Praise be to Allah , the cherisher and sustainer of the worlds).